2000
DOI: 10.1051/rnd:2000105
|View full text |Cite
|
Sign up to set email alerts
|

Uterine blood flow in sows: effects of pregnancy stage and litter size

Abstract: -Female pigs were assigned to three groups at 94 days of age: a control group (CTR), a group undergoing the ligation and severing of the left oviduct (LIG), and a group undergoing right hysteroovariectomy (HHO). They were inseminated at 307 days of age. At 35 days of pregnancy, an ultrasonic transit time flow probe was implanted around the middle artery of one uterine horn in 33 sows and uterine blood flow was measured during thirteen 24-h periods between 44 and 111 days. Despite large differences in ovulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 44 publications
3
62
0
2
Order By: Relevance
“…According to Zaleski and Hacker [26], this may reflect the quality of uterine support of the litter and the vigour of the litter at the onset of parturition. The decreased uterine space per foetus explains why piglets from large litters are lighter at birth [20]. Uterine space may partially be connected to sow body weight, which could explain the smaller uterine space of primiparous sows in comparison with multiparous animals [19].…”
Section: Discussionmentioning
confidence: 99%
“…According to Zaleski and Hacker [26], this may reflect the quality of uterine support of the litter and the vigour of the litter at the onset of parturition. The decreased uterine space per foetus explains why piglets from large litters are lighter at birth [20]. Uterine space may partially be connected to sow body weight, which could explain the smaller uterine space of primiparous sows in comparison with multiparous animals [19].…”
Section: Discussionmentioning
confidence: 99%
“…Convincing data revealed that development of Meishan conceptuses was more uniform between Days 8 and 14 of gestation (Bazer et al, 1988), and within-litter variation in birth weight was lower in Meishan litters than in Large White litters (Lee and Haley, 1995). Differences in growth patterns for placentas and uterine capacity (Père and Etienne, 2000) between the two breeds can account for a large portion of the significant differences in birth-weight distribution. The Meishan placentas are smaller at farrowing , while vascular density progressively increases between Days 90 and 110 of gestation with constant placental size.…”
Section: Breed Characteristicsmentioning
confidence: 97%
“…Such techniques can be applied to AGA, IUGR and LGA fetuses since they can be easily identified in the uterine horns during surgical intervention. To use all these techniques in one study is difficult and can be simplified by only using catheters (blood sample collections), since blood flow rates are available from other studies during several stages of pregnancy (177) . Scientists now have new tools such as genomic, proteomic and metabolomic techniques.…”
Section: Large For Gestational Agementioning
confidence: 99%